Design, synthesis, and pharmacological evaluation of 2-(4-sulfonylphenyl)-2-[(E)-pyrrolidin-1-ylimino]-N-thiazoleacetamides as glucokinase activators. Issue 15 (1st August 2020) - Sugama, Hiroshi; Matsudaira, Tetsuji; Yanagisawa, Hideyuki; Ohashi, Rikiya; Nawano, Masao; Yasuda, Kosuke; Takayama, Hiromitsu
Graphical abstract: Abstract: This paper presents the synthesis and glucokinase activity of novel hydrazone derivatives. The 2-(4-cyclopropylsulfonylphenyl)-2-[( E )-pyrrolidin-1-ylimino]-acetamide derivatives 5a –5h presented the in vitro glucokinase activities and in vivo blood glucose-lowering effects in mice. Particularly, 5h showed an oral hypoglycemic effect in rats at 1 mg/kg. These hydrazone derivatives are a potential new class of glucokinase activators for the treatment of type 2 diabetes.